Can LADM contribute to a fair large scale land acquisition? - Hespanha, João Paulo (2013)
Large scale land acquisitions happen again and again. Reasons are in food prices, production of palm oil and bio fuel and carbon offset. Substantial areas are affected, e.g. areas in size comparable with Western Europe. Beneficiaries are local elites, national governments and international companies, harmed are small holders who can not defend their rights, esp. women. Oxfam (2011) provides analyses and a set of recommendations on this subject. In the context of those recommendations from Oxfam it can be recognised that there is an urgent need for new approaches in Land Administration and Management. Conventional approaches, often of historical footings, proved to be inadequate in many jurisdictions. Flexibility is needed in relation to the way of recordation1, the type of spatial units used, the inclusion of customary and informal rights, the data acquisition methodologies and in the accuracy of boundary delineation. It is less important to produce accurate maps. It is more important to have a complete cadastral index map and to know how accurate the map is. For instance, highly rigorous and accurate methodologies as practiced by registered or licensed surveyors are not pro-poor approaches and take very long to cover a whole region. A more flexible approach in Land Administration and Management may result in fast availability of a cadastral map with a related registry of all (formal, informal, customary) in an area. This can then be used as a (more) solid base for large scale land acquisitions. The paper investigates up to which level the Land Administration Domain Model (LADM) can contribute to a fair approach in large scale land acquisition. In the paper the problem of large scale land acquisition will be briefly introduced with a focus on the transfers of rights (and restrictions). Fitness for purpose will be tested based on a series of cases. The broader land governance issues that need to be addressed to get to fair large scale land acquisitions are only briefly mentioned and mostly outside the scope of this paper.